Creating Vlog as Media in English Language Teaching (ELT):Teaching Speaking - Anrasiyana Anrasiyana; Sulistyaningsih Sulistyaningsih; Abdul Syakur (Universitas Pahlawan Tuanku Tambusai, 2022)
In modern era, everything can be accessed by technology. One of the famous ones for young generation is YouTube or video blog (vlog) where someone can take a video for specific purposes. Google noted that there are 60% of people all over the world uploaded their activity in vlog and publish it in YouTube. Teaching speaking for students is not easy it needs huge extra to improve their speaking moreover in this global era where everything is measured by the achievement of the studentsThis research used to know the implementation of creating vlog in English Language Teaching (ELT). This research used qualitative descriptive in ilustrating the result. The subject of this research is the students of VI SDN Batang-Batang Daya 1. The instrument of this research are observation sheet, field note, in depth interview with the teacher and questionnaire for students. To analyze the data the researcher used descriptive qualitative. The result of this research described abot the implementation of creating video blogging (vlog) in English langage teaching (ELT) in teaching speaking.